A training programme for medical students in providing spiritual care to people with advanced diseases and their loved ones: A case study from the Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Poland - Fopka-Kowalczyk, Małgorzata; Groves, Richard; Larkin, Philip; Krajnik, Małgorzata (Frontiers in Cardiovascular Medicine, 2022)
Purpose This article presents the first programme on spiritual care particularly for people with advanced life-limiting illness including heart failure, lung disease or cancer for medical students in Poland implemented at the Collegium Medicum in Bydgoszcz of the Nicolaus Copernicus University in Toruń. Methods and materials Several steps were identified for the development of the first programme on spirituality for medical students at the Collegium Medicum in Bydgoszcz including preliminary work on the content of the programme, agreement on key concepts, terms, and definitions; consultations with teachers and review of the literature. Results The first Polish spiritual curriculum for medical students was implemented. The spirituality curriculum will potentially contribute to better care for the people with advanced illnesses such as heart failure, chronic lung disease or cancer and improve the quality of relationships between professionals and patients. Conclusion The article presents the content of the program, the expected learning objectives and ascribed teaching methods, along with the preliminary evaluation made by students.